Reproduction and conservation of the magdalena river turtle (podocnemis lewyana) in the claro cocorná sur river, colombia (2014)
The Magdalena River Turtle, Podocnemis lewyana, is an endangered and endemic turtle from Colombia. Among the most important information needed to conserve endangered species is to identify, monitor, and protect the sites used by the species to reproduce and grow. In this study we report, for the first time, the reproductive output and the nesting beaches of P. lewyana in the Claro Cocorná Sur River, a tributary of the Magdalena River drainage. We systematically examined a river transect of 8 km with 14 sandy beaches during two nesting seasons in one year. We recorded a yearly production of 47 clutches, 957 eggs, and two preferred nesting beaches: Alto Bonito with 51 %, and Bélgica with 28.3 % of this reproductive output. AAFUVER, a community-based organization, has led a headstarting program since 2010 to decrease in-situ egg mortality due to predation on nesting beaches. AAFUVER collects and incubates the eggs ex-situ, raises the hatchlings for one to five months and then releases them into the same river. To understand potential effects of such egg manipulation, we monitored and compared in-situ and ex-situ incubation temperatures. We found exsitutemperatures below the pivotal temperature known for P. lewyana and below the temperatures in nesting beaches. Finally, we monitored hatchlings growth under AAFUVER captive conditions, and found that hatchlings duplicated their body mass during the first three months of age. Egg weight was strongly associated to body weight at hatching, however this association is lost by the third month of age. We strongly encourage supporting this community-based conservation program, and the protection of the Claro Cocorná Sur River as an important nesting and growth habitat for the conservation of P. lewyana.Reproducción y conservación de la tortuga del Río Magdalena(Podocnemis lewyana) en el Río Claro Cocorná sur, ColombiaLa tortuga del Río Magdalena, Podocnemis lewyana, es una tortuga categorizada como amenazada y además endémicacolombiana. Dentro de la información más necesaria para entender el estado de conservación de estas especies esta elidentificar, monitorear y proteger sus sitios de reproducción y crecimiento. En este estudio se reporta, por primera vez, elpotencial reproductivo y las principales playas de anidación de P. lewyana en el río Claro Cocorná Sur, un tributario del ríoMagdalena. Un trayecto de 8 km del río que albergaba 14 playas arenosas fueron monitoreados sistemáticamente durante dos estaciones de anidación en un año. Durante este tiempose registraron 47 nidos, 957 huevos y dos playas demayor anidación: Alto Bonito con el 51 %, y Bélgica conel 28,3 % de dicha producción anual. AAFUVER, unaorganización de la comunidad local, ha liderado unprograma de reforzamiento poblacional para disminuirla mortalidad de los huevos incubados in-situ. AAFUVERcolecta e incuba los huevos ex-situ, cría los neonatos duranteuno a cinco meses, y los libera en el río de origen. Paraentender los efectos potenciales de esta manipulaciónde los huevos las temperaturas de incubación in-situ y exsitufueron monitoreadas y comparadas. Se encontró quelas temperaturas ex-situ son inferiores a la temperaturapivotal de P. lewyana y a las temperaturas en las playas deanidación. Finalmente, se reporta el crecimiento corporalde los tortuguillos dadas las condiciones de cautiverio deAAFUVER. Se encontró una fuerte asociación entre el pesodel huevo y el peso de los neonatos a los siete días de edad,sin embargo esta asociación se perdió a los tres meses deedad. Nosotros enfatizamos en la importancia de apoyareste programa de conservación liderado por la comunidadlocal, y la protección del Río Claro Cocorná Sur como unhábitat importante de anidación y crecimiento de P. lewyana